Wiki for knowledge sharing, a user-centred evaluation approach: a case study at STMicroelectronics. Issue 6 (7th October 2014) - Brichni, Manel; Mandran, Nadine; Gzara, Lilia; Dupuy-Chessa, Sophie; Rozier, David
Abstract : Purpose: – The purpose of this paper is to study how a Wiki is used for knowledge sharing within an organization. Design/methodology/approach: – The aim of this research is to evaluate this Wiki performance regarding knowledge sharing objectives. Findings: – A Wiki has been deployed since several years within STMicroelectronics Company to improve Business Intelligence teamwork. Originality/value: – The proposed evaluation methodology is based on a user-centered approach.